Tissue-dependent somaclonal mutation frequencies and spectra enhanced by ion beam irradiation in chrysanthemum - Okamura, Masachika; Hase, Yoshihiro; Furusawa, Yoshiya; Tanaka, Atsushi (Euphytica, 2015)
We investigated the effect of tissue source selection in combination with ion beam irradiation on generating flower-color mutants in Chrysanthemum morifolium . Flower color mutation in the chrysanthemum cultivar YoMystery (purple flowers) was used as an index to estimate mutation frequency and the spectrum of mutations. Somaclones regenerated from petal and leaf tissues and ion-beam irradiated clones derived from the two tissues were analyzed for stem length and flower color mutation. Three Gy of argon ion beams was regarded as an appropriate dose for irradiation because the resulting color mutants maintained an adequate stem length suitable for commercial use even with high mutation frequencies. Statistical analysis of 7,258 individuals from three separate experiments revealed that (1) somaclones from petal tissue had a higher mutation frequency (2.91 %, σ = 0.55) than leaf somaclones (2.01 %, σ = 0.26); (2) the effect of tissue source on the frequency of flower color mutations was significantly enhanced when combined with ion-beam irradiation in that the mutation frequency of ion-beam irradiated petal clones was 6.47 % (σ = 0.77), whereas that of ion-beam irradiated leaf clones was 3.89 % (σ = 0.52); and (3) the spectrum of carotenoid color mutations was remarkably increased by ion-beam irradiation in that both leaf and petal ion-beam irradiated clones had brown, red and yellow flowers in contrast to the somaclones that only produced yellow flowers. These results suggest that intentional or directed induction of flower color mutants with practical value is possible by combining tissue source selection with ion beam irradiation.